Novel Anti-Inflammatory Topical Herbal Gels Containing Withania somnifera and Boswellia serrata - S, Goyal (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTHerbal medicine has become an item of global importance both medicinal and economical. Although usage of these herbal medicines has increased, their quality, safety and efficiency are serious concerns in industrialized and developing countries. Plant play a vital role in curing various ailments of the man and herbal remedies are getting increasing patient compliance as they are devoid of typical side effects of allopathic medicines. The allopathic system of medicine includes two conventional line of the treatment for rheumatoid arthritis, which come along with certain side effects. Hence, turning to safe, effective and time tested ayuvedic herbal drug formulation would be a preferable option. So there is need to investigate such drugs and their effective formulation for the better patient acceptance. Considering these facts present review aims to develop novel herbal gel containing the herbs, viz Withania somnifera and Boswellia serrata. The present study deals that herbal gels formulation of the Withania somnifera and Boswellia serrata extract using different polymers as the gelling agents and different evaluation parameters provides the effective anti-inflammatory activity to treatment of the inflammation, pain, arthritis etc patients problems. This review focus on the current status of the therapeutic potential and phytochemical profile on the herbal anti –inflammatory agents as Withania somnifera and Boswellia serrata. It can also provides the better information regarding to the formulation and evaluation parameters of the novel herbal gel for anti-inflammatory activity and to provide the better therapeutic effects to patient compliance.